The Lab4P Consortium of Probiotics Attenuates Atherosclerosis in LDL Receptor Deficient Mice Fed a High Fat Diet and Causes Plaque Stabilization by Inhibiting Inflammation and Several Pro‐Atherogenic Processes. Issue 17 (19th July 2021) - O'Morain, Victoria L.; Chan, Yee‐Hung; Williams, Jessica O.; Alotibi, Reem; Alahmadi, Alaa; Rodrigues, Neil P.; Plummer, Sue F.; Hughes, Timothy R.; Michael, Daryn R.; Ramji, Dipak P.
Abstract : Scope: Previous studies show that Lab4 probiotic consortium plus Lactobacillus plantarum CUL66 (Lab4P) reduces diet‐induced weight gain and plasma cholesterol levels in C57BL/6J mice fed a high fat diet (HFD). The effect of Lab4P on atherosclerosis is not known and is therefore investigated. Methods and Results: Atherosclerosis‐associated parameters are analyzed in LDL receptor deficient mice fed HFD for 12 weeks alone or supplemented with Lab4P. Lab4P increases plasma HDL and triglyceride levels and decreases LDL/VLDL levels. Lab4P also reduces plaque burden and content of lipids and macrophages, indicative of dampened inflammation, and increases smooth muscle cell content, a marker of plaque stabilization. Atherosclerosis arrays show that Lab4P alters the liver expression of 19 key disease‐associated genes. Lab4P also decreases the frequency of macrophages and T‐cells in the bone marrow. In vitro assays using conditioned media from probiotic bacteria demonstrates attenuation of several atherosclerosis‐associated processes in vitro such as chemokine‐driven monocytic migration, proliferation of monocytes and macrophages, foam cell formation and associated changes in expression of key genes, and proliferation and migration of vascular smooth muscle cells. Conclusion: This study provides new insights into the anti‐atherogenic actions of Lab4P together with the underlying mechanisms and supports further assessments in human trials. Abstract : The Lab4P consortium of probiotics attenuates atherosclerosis in LDL receptor deficient mice fed a high fat diet and prevents multiple processes associated with disease progression in vitro. Upward arrow, increase; downward arrow, decrease. LDLr −/−, low density lipoprotein deficient mice.